2015
DOI: 10.1016/j.jcma.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous computed tomography-guided cryoablation for renal tumor: Experience in 30 cases

Abstract: Computed tomography-guided percutaneous cryoablation is a safe and effective technique for treating renal tumors with excellent renal function preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There was a significant difference in the tumor size between the two groups in this study (P < 0.05, Mann-Whitney U test). Minimally invasive treatment, such as RFA and cryoablation, are established modalities for the treatment of small RCC without distant metastasis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The absence of distant metastasis should be confirmed before minimally invasive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant difference in the tumor size between the two groups in this study (P < 0.05, Mann-Whitney U test). Minimally invasive treatment, such as RFA and cryoablation, are established modalities for the treatment of small RCC without distant metastasis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The absence of distant metastasis should be confirmed before minimally invasive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of minimally invasive treatments such as radiofrequency ablation (RFA) and cryoablation for T1a (tumor size 4 cm) renal cell carcinoma (RCC) without distant metastasis has been gradually increasing (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The potential advantages of these procedures are good local control and a minimally invasive approach.…”
Section: Introductionmentioning
confidence: 99%
“…MIP is also a popular affinity ligand for electrochemical dopamine sensing, especially when combined with nanomaterials such as graphene, 131 CNTs, 132 QDs, 77 and NPG 133 . An electrochemical sensor displaying improved selectivity and sensitivity by Yang and co‐workers is shown in Figure 7B.…”
Section: Electochemical Biosensors Based On Oxidation Of Dopaminementioning
confidence: 99%
“…Our study showed that PAS after renal cryoablation was generally early-onset and self-limiting with minimal effects on lifestyle and had mostly resolved by day 8. Recognition of the onset, severity, and duration of PAS may be helpful in distinguishing PAS from complications that show similar symptoms, such as urinary tract infection [14,15] and perirenal abscess [16,17], thereby facilitating prompt treatment of such complications.…”
Section: Discussionmentioning
confidence: 99%